Prenatal diagnosis and molecular cytogenetic characterization of mosaicism for a small supernumerary marker chromosome derived from ring chromosome 4 - Chih-Ping Chen; Ming Chen; Yi-Ning Su; Fuu-Jen Tsai; Schu-Rern Chern; Pei-Chen Wu; Wen-Lin Chen; Li-Feng Chen; Chen-Wen Pan; Wayseen Wang (Elsevier, 2011)
Objective: To present prenatal diagnosis and molecular cytogenetic characterization of mosaicism for a small supernumerary marker chromosome (sSMC) derived from ring chromosome, or r(4) by spectral karyotyping (SKY), fluorescence in situ hybridization (FISH), and array comparative genomic hybridization (aCGH). Materials, Methods, and Results: A 37-year-old, primigravid woman underwent amniocentesis at 18 weeks of gestation because of advanced maternal age. Amniocentesis revealed a de novo ring-shaped sSMC in 16 of 31 amniocyte colonies. The parental karyotypes were normal. Level II ultrasound findings were unremarkable. Repeated amniocentesis revealed a karyotype of 47,XX,+mar[17]/46,XX[19]. The sSMC was characterized by SKY and FISH, which showed a chromosome 4 origin of the sSMC. aCGH demonstrated a 21.7-Mb gain in the gene dosage encompassing the region of 4p12→q13.2. The sSMC was r(4)(p12q13.2). The fetal karyotype was 47,XX,+r(4)(p12q13.2)[17]/46,XX[19]. The pregnancy was subsequently terminated. The fetus postnatally manifested hypertelorism, epicanthic folds, a prominent nose, a triangular face, low-set ears, clinodactyly of the fingers, and small big toes. Postnatal cytogenetic analyses of fetal and extraembryonic tissues revealed the karyotypes of 47,XX,+r(4)[18]/46,XX[21] in cord blood, 47,XX,+r(4)[20]/48,XX,+r(4),+r(4)[1]/46,XX[9] in umbilical cord, 47,XX,+r(4)[14]/47,XX,+dic r(4)[1]/46,XX[25] in skin, 47,XX,+r(4)[15]/46,XX[25] in amnion, and 47,XX,+r(4)[12]/47,XX,+dic r(4)[1]/46,XX[2] in placenta. Conclusion: SKY, FISH, and aCGH are helpful in genetic counseling of prenatally detected sSMCs by providing the immediate and thorough information on the origin and genetic component of the sSMC.